Electrochemical measurements of synthesized nanostructured β Ni(OH)2 using hydrothermal process and activated carbon based nanoelectroactive materials - 1. S. Kettaf, O. Guellati, A. Harat, H. Kennaz, D. Momodu, J. Dangbegnon, N. Manyala, and M. Guerioune (SN Applied Sciences, 2019)
In this investigation, nickel hydroxide Ni(OH)2 based nanostructured materials were synthesized by simple and low cost free template hydrothermal method at two different growth temperatures with and without SDS surfactant. The X-ray diffraction, Raman spectroscopy and field emission scanning electron microscopy analysis confirmed the formation of β-Ni(OH)2 pure brucite crystalline phase in spherical nanoparticle morphology with an average diameter ranging from 8 to 27 nm. In the second step, these nanospherical agglomerated hydroxide particles with activated carbon addition were performed as electroactive materials deposited on nickel foam current collector as working electrodes. The electrochemical tests in a three-electrode configuration using 6 MKOH electrolyte show that the best electroactive NPs (βbc-Ni(OH)2 and β-Ni(OH)2 obtained at optimized conditions, have a maximum specific capacitance (Cs) of 4697 F g−1 and 3431 F g−1 at 5 mV s−1 scan rate with a specific capacity (Qs) of 744 mAh g−1 and 618 mAh g−1 at 1 A g−1 current density with an Rs of about 0.24 and 0.28 Ω, respectively. At 30 A g−1 after 1700 cycles, the coulombic retention is around 99.06% (or capacity retention 109 mAh g−1), demonstrating remarkable cycling stability for Ni based hydroxide.